تجلّيات البنية الفنّية في شعر ابن الرومي - بالحاج, عباس (جامعة الوادي - University of Eloued, 2021)
تعدّ البنية الفنية وسيلة أساسية في التشكيل الشعري، وقد حازت اهتماما كبيرا لدى الباحثين والدّارسين منذ القديم إلى يومنا هذا. وموضوع بحثنا هذا يتمحور حولها، وهو في شعر ابن الرومي، وهذا كلّه بغية الكشف عن بنية القصيدة عند الشّاعر وبهدف الوقوف عند أهمّ خصائصها الفنية. وقد ارتكزنا في ورقتنا البحثية هاته على المنهج الوصفي التحليلي، والذي أضفى بنا إلى طرح بعض الإشكالات التي كان أهمها: فيم تتجلى بنية القصيدة في شعر ابن الرومي؟ وما طبيعة استهلال القصيدة عنده؟ وما أهم الوجوه البيانية والخصائص الأسلوبية في شعره؟ كما ابتغينا الوصول إلى إظهار مدى براعة الشّاعر وموهبته في توضيح الجوانب الفنية والأسلوبية في شعره . It is crucial to look at the techniques thatapoet has used to compose hispoem. Therefore, manyresearchers have traditionallyfocused on analyzing the aesthetic of a poem. This study aimsatshedding light on the structure of Ibn Al Rumipoems. Also, the study examines the distinctive techniques heused in composinghispoems. Moreover, the methodused to conductthis research is descriptive-analytical whichled to ask questions such as: how is the poetic structure manifested in Ibn Al-Rumipoetry? Whatis the nature of initialization in hispoetry? What are the main figures of speech and stylisticdevices in hispoetry? The study reveals how Ibn Al-Rumiwaswizard and talentedatclarifyingaesthetic and stylistic aspects in hispoetry.
مقال
Keywords: بنية فنية ; قصيدة ; ابن الرومي ; خصائص أسلوبية ; وجوه بيانية; AestheticStructure,poetry ; Ibn Al Rumi ; Figures of speech ; Sylistic characteristics